Enhancing Future Educators' Competencies Through Field Introduction Programs: A Qualitative Analysis - Nur Efendi (Indonesian Journal of Cultural and Community Development, 2023)
This study aimed to analyze the implementation and outcomes of the Pengenalan Lapangan Persekolahan (PLP) 2 course at Muhammadiyah 6 Junior High School (SMP) in Krian, Sidoarjo, conducted by students from the Faculty of Psychology and Education at Muhammadiyah University of Sidoarjo (UMSIDA). The research utilized a qualitative descriptive method, examining data from documentation, observation, interviews, and questionnaires. The study assessed the competencies of aspiring educators (teachers) in pedagogical, personality, social, and professional aspects. The results indicated that students achieved satisfactory competence levels (individual and classically) in all four domains, enabling them to effectively carry out teaching functions and enhance students' learning outcomes. Moreover, the respondents' positive responses, with high interest and motivation in the course, indicated their readiness to manage classroom activities, leading to improved student competencies. This study contributes valuable insights into the preparation and quality improvement of future educators through field introduction programs. Highlight: Effective Implementation: The study analyzes the outcomes of the Pengenalan Lapangan Persekolahan (PLP) 2 course, which successfully prepares aspiring educators to become competent teachers through qualitative descriptive research. Enhanced Student Competencies: The research demonstrates that students achieved satisfactory competence levels in pedagogical, personality, social, and professional aspects, leading to improved learning outcomes and academic competitiveness. Positive Student Response: The study reveals that students showed high interest and motivation in the course, indicating their readiness to manage classroom activities and enhance the quality of student competencies. Keyword: Education Quality, Teacher Preparation, Field Introduction Program, Competence, Student Response